Adsorption of methylene blue from aqueous solution using untreated and treated (Metroxylon spp.) waste adsorbent: equilibrium and kinetics studies - Amode, Jeminat O.; Santos, Jose H.; Alam, Md Zahangir; Mirza, Aminul H.; Mei, Chan C. (2016)
Background (Metroxylon spp.) waste is an inexpensive and abundantly available material with the characteristics of a good adsorbent for treating dye from wastewater. We studied the effectiveness of alkali and acid modiﬁcation in enhancing the adsorption capacity of sago waste. The untreated and treated adsorbent was characterized by FTIR, elemental analysis and BET surface area. The capacity of each adsorbent to adsorb MB was evaluated at different pH values, adsorbent dosage and initial dye concentrations and contact time. Results According to the results obtained, alkali treatment more than doubled the sorption capacity of sago waste by increasing the porosity, surface area and number of adsorption sites. The alkali-treated material also adsorbed signiﬁcantly more than many known biosorbents. The effects of the initial concentration of methylene blue, solution pH and adsorbent dosage on methylene blue removal are reported. Equilibrium data were best represented by the Langmuir isothermmodel with adsorption capacities of 83.5, 212.8 and 36.82 mg/g for untreated, potassium hydroxide-treated and phosphoric acid-treated sago wastes, respectively. The kinetics of adsorption were best described by a pseudo-second-order model (R2 = 0.999). Conclusions The alkali treatment of sago waste demonstrates the use of a low-cost agricultural waste and a simple